Circulating tumor DNA in diffuse large B-cell lymphoma: analysis of response assessment, correlation with PET/CT and clone evolution - Guilherme Duffles; Jersey Heitor da Silva Maués; Fernanda Lupinacci; Luciana Guilhermino Pereira; Elisa Napolitano Ferreira; Leandro Freitas; Fernanda Niemann; Maria Emilia Seren Takahashi; Celso Darío Ramos; Maria de Lourdes L. Ferrari Chauffaille; Irene Lorand-Metze (Hematology, Transfusion and Cell Therapy)
Introduction: Circulating tumor DNA (ctDNA) can be obtained from cell-free DNA (cfDNA) andis a new technique for genotyping, response assessment and prognosis in lymphoma. Methods: Eighteen patients with samples at diagnosis (ctDNA1), after treatment (ctDNA2) and extracted from diagnostic tissue (FFPE) were evaluated. Results: In all patients, at least one mutation in cfDNA was detected at diagnosis. CREBBP was the most frequent mutated gene (67 %). In 12 of the 15 patients with complete remission, the mutation attributed to the disease found at diagnosis cleared with treatment. A reduction in the ctDNA was observed after treatment in 14 patients, 12 of whom achieved complete remission. Correlations were found between the ctDNA at diagnosis and total metabolic tumor volume (r = 0.51; p-value = 0.014) and total lesion glycolysis 2.5 (r = 0.47; p-value = 0.024) by PET at diagnosis and between ctDNA at diagnosis and radiomic features of the lesions with the largest standardized uptake value. There was a strong inverse correlation between ΔctDNA1 and ΔSUVmax by PET/CT (r = −0.8788; p-value = 0.002). Conclusion: Analysis of ctDNA and PET/CT in large B-cell lymphoma are complementary data for evaluating tumor burden and tumor clearance after treatment. Analysis of radiomic data might help to identify tumor characteristics and their changes after treatment.